The Effect of Silicon Deficiency on Material Properties of Noduar Cast Iron - S.D. Rasika Perera (OUSL Journal)
The brittle failure of a crankshaft was investigated. The chemical composition and material properties of the crankshaft were analyzed. The hardness profile indicated that the manufacturer used the crankshaft as cast without heat treatment. The chemical composition and material parameters were compared with those found in the literature for similar applications. The yield strength, tensile strength, and hardness values observed for the crankshaft were lower than those observed in other crankshafts in the literature. The chemical analysis revealed that the Si composition deviated from the composition in the literature for a typical crankshaft material. Furthermore, low modularity and irregular nodule distribution were observed. The main reason for this failure was the poor mechanical properties arising from the chemical composition, processing, and inoculation characteristics.